2002
DOI: 10.1073/pnas.052705399
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterium tuberculosis WhiB3 interacts with RpoV to affect host survival but is dispensable for in vivo growth

Abstract: Previous work established that the principal sigma factor (RpoV) of virulent Mycobacterium bovis, a member of the Mycobacterium tuberculosis complex, restores virulence to an attenuated strain containing a point mutation (Arg-5153 His) in the 4.2 domain of RpoV. We used the 4.2 domain of RpoV as bait in a yeast two-hybrid screen of an M. tuberculosis H37Rv library and identified a putative transcription factor, WhiB3, which selectively interacts with the 4.2 domain of RpoV in virulent strains but not with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
210
2
2

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 223 publications
(232 citation statements)
references
References 38 publications
(37 reference statements)
15
210
2
2
Order By: Relevance
“…The mycobacterial growth rate in guinea pigs is not the only indicator of virulence, and studies have shown that strains with no differences in in vivo growth rates can produce infections that differ significantly by histopathological analysis 46,47 . Despite the reduced bacterial loads, histopathological assessments revealed that lung sections from guinea pigs infected with DmazF3D9D6 exhibited higher degrees of granulomatous inflammation than guinea pigs infected with the parental strain (Fig.…”
Section: Mazf Ribonucleases Are Required For Persistence In Vitromentioning
confidence: 99%
“…The mycobacterial growth rate in guinea pigs is not the only indicator of virulence, and studies have shown that strains with no differences in in vivo growth rates can produce infections that differ significantly by histopathological analysis 46,47 . Despite the reduced bacterial loads, histopathological assessments revealed that lung sections from guinea pigs infected with DmazF3D9D6 exhibited higher degrees of granulomatous inflammation than guinea pigs infected with the parental strain (Fig.…”
Section: Mazf Ribonucleases Are Required For Persistence In Vitromentioning
confidence: 99%
“…S. coelicolor whiB mutants produce abnormally long, tightly coiled aerial hyphae that are completely blocked in their ability to form sporulation septa (Chater, 1972;Davis & Chater, 1992;Flardh et al, 1999). Studies of whiB orthologues in mycobacteria have shown that the M. smegmatis whiB2 gene (also called whmD) is essential ; M. tuberculosis whiB3 plays a role in virulence and its gene product may interact with a sigma factor of RNA polymerase (Steyn et al, 2002); whiB7 of M. tuberculosis is involved in multi-drug resistance (Morris et al, 2005). Each of the Wbl family of proteins contains four invariant cysteine residues, which are believed to be involved in binding a [4Fe-4S] cluster (Jakimowicz et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…It is worthy to note that the results of these studies revealed that the end of the in vivo exponential growth phase of M. tuberculosis in the lungs of infected mice coincides with the bacillary load-independent downregulation of all the host genes studied. Recently, characterization of the M. tuberculosis WhiB3 mutant has provided evidence that the tubercle bacillus can profoundly affect the host immune response independent of tissue bacillary load (Steyn et al, 2002). The significance and specificity of the downregulation of host gene expression observed at 25 days post infection in the present study can be better assessed using the microarray technology.…”
Section: Analysis Of the Relative Expression Of Host Immunolgical Genmentioning
confidence: 67%